ANALISIS KUALITAS SDM PENGELOLA LAPORAN KEUANGAN DAN PENGEMBANGAN USAHA BUMDES DI DESA BOTTOMALLANGGA ENREKANG - Dewi Khaerani Herman; Syarifuddin Yusuf; Akhsan Akhsan; Sariana Damis (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis, 2026)
The purpose of this study is to evaluate the performance of Village-Owned Enterprises (BUMDes) in Botto Mallangga Village, investigate the factors that influence the low performance of BUMDes, and identify existing business obstacles and opportunities. The benefits of this study for the village community are improving the quality of public services and infrastructure through better management of Village Funds and BUMDes, encouraging active community participation in the management and development of BUMDes for the common good. Practically, this study provides guidance for BUMDes managers in Botto Mallangga Village to improve transparency, accountability, and professionalism in managing village finances and resources. The object of this study is BUMDes Bottomallangga. Data collection techniques used in this study were interviews, observation, and documentation. Data analysis used in this study was qualitative descriptive analysis. After conducting the analysis process, it was found that the quality of Human Resources (HR) in BUMDes Bottomallangga is still limited, especially in terms of managing financial reports. Most BUMDes managers do not have experience in economics education, nor have they ever participated in practices related to financial management. This results in financial report management that is still done manually without utilizing technology. The development of BUMDes business units has also experienced a decline, caused by the emergence of competitors and internal problems.